Integrasi Quality Function Deployment (QFD) dan Conjoint Analysis untuk Mengetahui Preferensi Konsumen - Desrina Yusi Irawati; Moses Laksono Singgih; Bambang Syarudin (Jurnal Optimasi Sistem Industri, 2016)
The advantages of QFD is to translate customer need into a technical response. But QFD has some disadvantages related to the difficulties in distinguishing the difference of needs between consumers, difficulties to fulfill the needs of different consumer groups, and the exietence of conceptual gap between consumers and companies. The proposed method to overcome these disadvantages is conjoint analysis. The main advantage of conjoint analysis is the ability to get the optimal design combination for products or services based on consumers' preference. The result of conjoint analysis, estimation of perceived value, and integration of QFD can be used to know the preference market needs among consumers, identify the office desk, determine consumer segments and technical respons, and estimate the additional price of office desk attributes as an effort to the development of the office desk. In overall the best Office desk combination results based on consumers' preference of Office desk is the white color without additional drawers or supporting features, with table size is 120x60x75 cm and footstool. Segmentation based on preferences resulting in three clusters, namely size, color, and availability of drawer. The highest technical response to be the company's priority in meeting the needs of consumers is to make the proper hole connection. Based on the perceived value, the company is capable to predict that the additional prices of 1 drawer is Rp.1-Rp.500.000, the addition price of 2 drawers is Rp.800,000 - Rp.900.000, and the addition price of the foundation of the foot is Rp.50.000 - Rp.150.000, and the additional price of supporting features is Rp.150.000-Rp.250.000.